PREDICTIVE MAINTENANCE IMPLEMENTATION OF AUTOCLAVE REACTOR AGITATOR - Oktafianus Toding; Dayal Gustopo Setiadjit; Fuad Achmadi (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Machines are an important factor in the industrial world to produce a product in a company. PT. XYZ is a company engaged in the food industry for sweeteners processed from tapioca flour and corn flour where, through research observations, data is obtained that there are problems that are often faced such as damage to the Agitator Autoclave machine, unavailability of spare parts ( spare parts) needed when there is a breakdown and a breakdown schedule for maintenance workers who have to work overtime. The purpose of this study is to determine the current condition of machine maintenance to reduce damage or failures, the level of machine effectiveness and provide alternative solutions to increase machine effectiveness. The research method used is quantitative using the Overall Equipment Effectiveness (OEE) method, Six Big Losses, Failure Modes and Effects Analysis. The results of the study resulted in an Overall Equipment Effectiveness (OEE) value of 75.07%. The low OEE value on the Agitator Autoclave machine is due to the low performance factor because the engine speed does not match its ideal speed and also the low idle and minor losses in the losses factor caused by frequent breakdowns. Suggestions and suggestions that can be recommended are to periodically evaluate machines and replace old machines.